Judges' Efforts to Uphold the Principles of Legal Justice and Human Rights in Imposing Sanctions in Drug Cases - Septian, Nurul Naeni; Pangastuti, Inagatha Setyarahma (JURNAL USM LAW REVIEW, 2024)
This study aims to analyze whether court decisions in drug abuse cases are based on Indonesia's principles of justice and human rights. This study is important to conduct because there are quite significant differences in the sanctions received by perpetrators of drug crimes, giving rise to the perception that judges are inconsistent in providing fair decisions for perpetrators of drug crimes. In their decisions, judges often ignore the principles of human rights to provide a deterrent effect to perpetrators of drug crimes. Hence, the assumption arises that judges in many cases discriminate against defendants of drug crimes. This study uses a normative legal approach and case studies to examine the case submitted in decision number 1041/Pid.Sus/2024/PN.Sby. Based on these findings, the judge attempts to uphold a fair decision by imposing a sentence commensurate with the error and considering the economic ability of the perpetrator to pay the fine, with the option of additional imprisonment for six months if unable to pay. This decision approach aims to uphold the principles of human rights. Keywords: Drug Abuse; Human Rights; Principle of Justice